RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND HISTORY OF CHILDBIRTH COMPLICATIONS WITH TODDLERS DEVELOPMENT - Idola Perdana Sulistyoning Suharto; Endang Mei Yunalia; Priska Emiliana; Lisna Watie Geragam; Yohanes `Tatan (Gaster, 2023)
Background : Development is an increase in body functions and structures that are more complex in the ability of gross motion, fine motion, speech and language, as well as socialization and independence. More than 200 million children under five are found to be developing not according to age. Objective : The purpose of this study are to analyze the relationship between nutritional status and child development and to analyze the relationship between history of childbirth complications and child development. Method : This research was conducted in Bujel, Kediri City. The study began in April 2022. This study was a correlative analytic study. The sample in this study was some of the toddlers in Bujel as many as 45 toddlers. The research data was tested with Spearman's rho. Result : The results of the Spearman's Rho test between the variables of nutritional status and child development is 0.001, and between history of childbirth complications and child development is 0.024. Conclusion and Suggestions : The conclusions of this study are there is a relationship between nutritional status and the development of toddlers in Bujel, Kediri City. Another conclusion is that there is a relationship between the history of childbirth complications and the development of children under five in Bujel, Kediri City. It is hoped that the respondent's parents pay more attention to nutritional status so that the child's development is optimal.